2009
DOI: 10.1089/jir.2008.0092
|View full text |Cite
|
Sign up to set email alerts
|

The Induction of Type I Interferon Production in Hepatitis C–Infected Patients

Abstract: Chronic infection with hepatitis C virus (HCV) is a major global health problem. One way HCV may evade the host immune response is by inhibiting the production of type I interferon (IFN). In addition, the standard treatment for chronic HCV infection involves treatment with IFN-alpha (or its pegylated derivative), alone or in combination with ribavirin. Therefore, it is believed that an important reason that most HCV-infected individuals progress from acute to chronic infection is due to a defect in the host re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
3
13
1
Order By: Relevance
“…Consequently, expressed ISGs can originate from the detectable, but low level of IL28A produced during early antiviral phase mediated by CARDIF or from extrahepatic sources of IFN (e.g., infiltrated immune cells) that act in a paracrine manner through the Jak-STAT signal transduction pathway. IFN levels are indeed detected in serum of 43% of chronically HCV-infected patients suggesting that some patients are able to trigger an initial immune response consistent with the intrahepatic ISGs upregulation observed in this study and described previously [31]. Moreover, experiments using paired liver biopsies and PBMCs collected from HCV-infected patients demonstrated upregulated ISGs -but not IFN genes -in liver biopsies [32,33] in contrast to induction of both ISGs and various type I IFN subtypes in circulating PBMCs.…”
Section: Discussionsupporting
confidence: 89%
“…Consequently, expressed ISGs can originate from the detectable, but low level of IL28A produced during early antiviral phase mediated by CARDIF or from extrahepatic sources of IFN (e.g., infiltrated immune cells) that act in a paracrine manner through the Jak-STAT signal transduction pathway. IFN levels are indeed detected in serum of 43% of chronically HCV-infected patients suggesting that some patients are able to trigger an initial immune response consistent with the intrahepatic ISGs upregulation observed in this study and described previously [31]. Moreover, experiments using paired liver biopsies and PBMCs collected from HCV-infected patients demonstrated upregulated ISGs -but not IFN genes -in liver biopsies [32,33] in contrast to induction of both ISGs and various type I IFN subtypes in circulating PBMCs.…”
Section: Discussionsupporting
confidence: 89%
“…Both IFN-a and IFN-c have been observed in sera from patients with CHC [21,22]. Their production may be induced by a host response to HCV within the liver, which would make these IFNs detectable in the systemic circulation of patients with CHC.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that NK cells from patients with CHC display a higher level of STAT1 expression than those from HS [24] and suggested that the up-regulation of STAT1 expression might result from a host response to HCV infection with IFN-a and/or IFN-c production, because STAT1 itself is one of the IFN-stimulated genes (ISGs) whose expression is up-regulated by IFN-a or IFN-c [27,28], which has been reported to be detected in the sera of patients with CHC [29,30]. The present study has shown that both NK cell subsets from the patients with CHC displayed a higher level of STAT1 expression than those from the HS (Fig.…”
Section: Discussionmentioning
confidence: 99%